2015
DOI: 10.1515/popore-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal (1960–2011) shoreline changes in Isbjørnhamna (Hornsund, Svalbard)

Abstract: A section of a gravel−dominated coast in Isbjørnhamna (Hornsund, Svalbard) was analysed to calculate the rate of shoreline changes and explain processes controlling coastal zone development over last 50 years. Between 1960 and 2011, coastal landscape of Isbjørn− hamna experienced a significant shift from dominated by influence of tide−water glacier and protected by prolonged sea−ice conditions towards storm−affected and rapidly changing coast. Information derived from analyses of aerial images and geomorpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…For instance, intensified erosion of shores has led to destruction of settlement infrastructure and has compromised community safety in dozens of Alaskan settlements (Gibbs, Harden, Richmond, & Erikson, ; Smith & Sattineni, ), for example, Shishmaref, Kivalina, and Unalakleet forcing unwanted relocation. Severe coastal erosion threatens also Tuktoyaktuk, Canada (Andrachuk & Pearce, )—the main port of western Canadian Arctic; oil storage facilities at Varandei, Pechora Sea coast (Guégan, Sinitsyn, Kokin, & Ogorodov, ); or infrastructure of Polish Polar Station in Hornsund, Svalbard (Zagórski et al, ). Arctic coastal settings are threatened not only by erosion.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, intensified erosion of shores has led to destruction of settlement infrastructure and has compromised community safety in dozens of Alaskan settlements (Gibbs, Harden, Richmond, & Erikson, ; Smith & Sattineni, ), for example, Shishmaref, Kivalina, and Unalakleet forcing unwanted relocation. Severe coastal erosion threatens also Tuktoyaktuk, Canada (Andrachuk & Pearce, )—the main port of western Canadian Arctic; oil storage facilities at Varandei, Pechora Sea coast (Guégan, Sinitsyn, Kokin, & Ogorodov, ); or infrastructure of Polish Polar Station in Hornsund, Svalbard (Zagórski et al, ). Arctic coastal settings are threatened not only by erosion.…”
Section: Resultsmentioning
confidence: 99%
“…The highest erosion rate in the Arctic was registered on Alaskan coast (Drew Point) with a value of −8.4 m/year, while the lowest erosion rate was reported in Svalbard. Other reported erosion rates in Svalbard range from −0.5 to −4.5 m/year for Longyearbyen [21], −0.26 m/year for Isbjørnhamna [48], −0.34 m/year and −0.47 m/year for ice-poor cliffs and ice-rich cliffs, respectively [32]. With a value of EPR of −0.21 m/year, our study area can be framed in around the average erosion rate previously reported in Svalbard.…”
Section: Shoreline Displacementmentioning
confidence: 99%
“…Terminus positions were mapped by tracing the waterline along the terminus in each image, then projecting those pixel coordinates onto a horizontal plane at an altitude of 0 m (tidal heights were not available) to convert them to world coordinates. Standard errors of 0.47 m in water level due to tides (Zagórski et al, 2015;Michał Ciepły, personal communication, 2012), 0.68 pixels due to uncertainties in terminus tracing, and 3.23, 5.70, and 10.53 pixels for each of the three cameras due to uncertainties in camera calibration and orientation result in standard errors for width-averaged glacier length of 3.79, 3.37, and 14.54 m, respectively.…”
Section: Front Positionsmentioning
confidence: 99%